"I am married, my dearest Susan, – I look upon it in that light": Fanny Burney´s court experience followed by reintegration with society - Ozarska, Magdalena (Univerzita Pardubice, 2009)
The journals and letters of novelist Frances Burney (1752-1840) have attracted increasing attention on the surge of revisionist approaches to English literary canon and feminism-driven rediscovery of the somewhat forgotten female authors of the past epochs. My intention is to demonstrate that Burney's journals and letters covering the periods before, during and after which she stayed at the royal court of King George III and Queen Charlotte (1786-1791) as Second Keeper of the Robes to the latter, provide ample illustration of the writer's mental isolation while seemingly finding herself in an environment particularly conducive to sociability.
Keywords: 18 century; life-writing; Frances Burney